Turizem in slovenska etnologija in kulturna antropologija v razmerju do mednarodne antropologije turizma in turističnih študij - Kravanja, Boštjan (Glasnik Slovenskega etnološkega društva, 2022)
The aim of this contribution is to provide insight into some aspects of the manifestation of tourist subjects in Slovenian ethnology and cultural anthropology. Predominantly, it deals with comparison between classical representations of heritage, its potentials and use in tourism on one hand, and research of sociocultural perspectives of tourist destinations and practices related to travelling on the other. In the article, this duality of Slovenian research of tourism is compared to the basic turning points in international anthropology of tourism.
Keywords: anthropology of tourism; antropologija turizma; cultural heritage; ethnology of tourism; etnologija turizma; folklorism; kulturna dediščina; tourist destination; turistična destinacija